Laboratory investigation of the relationship between electrical resistivity and geotechnical properties of phosphate tailings. (October 2018) - Chen, Yulong; Wei, Zuoan; Irfan, Muhammad; Xu, Jiajun; Yang, Yonghao
Highlights: The electrical resistivity of phosphate tailings was measured by laboratory tests. Effects of moisture content, dry density, temperature and other factors. A triaxial apparatus was modified. The relationship between electric resistivity and shear strength characteristics. Abstract: Electrical conductivity of soil can be considered as a proxy of soil physical properties. Due to its non-destructive nature, electrical resistivity method is serving as an attractive tool in geotechnical engineering practice. In this study, the electrical resistivity of phosphate tailings was measured by laboratory tests using two-phase electrode method. The effects of moisture content, dry density, temperature and other factors on the electric resistivity of phosphate tailings were examined in detail. The electrical resistivity of phosphate tailings was found to decrease with increase in water content, dry density and temperature. A triaxial apparatus was modified to study the relationship between electric resistivity and shear strength characteristics of phosphate tailings. Triaxial shear tests were conducted on the phosphate tailings specimens to determine the stress-strain response, variation in the shear strength parameters ( c and φ ) and the corresponding changes in electric resistivity. The initial electric resistivity of phosphate tailings specimens correlated negatively with shear strength, cohesion and internal friction angle. During the course of triaxial shear tests, electric resistivity of phosphate tailings decreased continuously with the increase in strain. However the rate of decrease became larger with yielding of the specimen. Consolidation tests were conducted by a modified oedometer to correlate electrical resistivity with consolidation pressure, compression coefficient and compression modulus. The electrical resistivity was found to decrease at a decreasing rate with consolidating pressure. Further, it increased with compression coefficient, but decreased with the increase of compression modulus of soil specimen. The work done in this study can be beneficial for robust estimation of in-situ properties, as well as for the evaluation of shear strength characteristics of phosphate tailings by means of electrical resistivity measurement.